Новые аспекты решения проблемы индикации и измерения геопатогенных и аномальных зон = New aspects of solving the problem indication and measurements and geopathogenic anomalous zones - Klimentov, V. V.; Prohorov, G. V.; Gozhenko, S. A.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Klimentov V. V., Prohorov G. V., Gozhenko S. A., Zukow W. Новые аспекты решения проблемы индикации и измерения геопатогенных и аномальных зон = New aspects of solving the problem indication and measurements and geopathogenic anomalous zones. Journal of Education, Health and Sport. 2015;5(4):109-116. ISSN 2391-8306. DOI: 10.5281/zenodo.16658 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A109-116 https://pbn.nauka.gov.pl/works/553461 http://dx.doi.org/10.5281/zenodo.16658 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.03.2015. Accepted: 27.03.2015. НОВЫЕ АСПЕКТЫ РЕШЕНИЯ ПРОБЛЕМЫ ИНДИКАЦИИ И ИЗМЕРЕНИЯ ГЕОПАТОГЕННЫХ И АНОМАЛЬНЫХ ЗОН NEW ASPECTS OF SOLVING THE PROBLEM INDICATION AND MEASUREMENTS AND Geopathogenic anomalous zones В. В. Климентов, Г. В. Прохоров, С. А. Гоженко, В. Жуков V. V. Klimentov, G. V. Prohorov, S. A. Gozhenko, W. Zukow Научный парк «Профилактическая медицина и охрана труда – новейшие системы и технологии», Одесса Черновицкий национальный университет им. Ю. Федьковича Украинский НИИ медицины транспорта, Одесса Uniwersytet Kazimierza Wielkiego, Bydgoszcz Science park «Preventive Medicine and Health - The latest systems and technologies ", Odessa Chernivtsi National University Yu. Fedkovicha Ukrainian scientific-research institute of transport medicine, Odessa Kazimierz Wielki University, Bydgoszcz Abstract The article deals with the creation of prerequisites for hardware and software system for the study of abnormal and geopathic zones. Analyzes the currently used instruments for detection and measurement of parameters and characteristics of pathogenic influences in anomalous zones. The author's methodology that combines the method of multi-channel measurements of physical quantities with mathematical methods of statistical analysis, since the methods and instruments used for this purpose now, in principle, not reliably determine their qualitative and quantitative parameters of such zones. The proposed approach to the problem is promising interdisciplinary study of natural phenomena. Keywords: appliance, anomalous zones, geopathic zones, Schumann resonances, electromagnetic field, software and hardware, micropulsations, stochastic resonance. Реферат В статье рассматриваются предпосылки создания программно-аппаратного комплекса для исследования аномальных и геопатогенных зон. Анализируются применяемые в настоящее время приборы для индикации и измерения параметров и характеристик патогенных воздействий в аномальных зонах. Предлагается авторская методология, позволяющая объединить метод многоканальных измерений физических величин с математическими методами статистического анализа, поскольку методики и приборы, используемые для этой цели в настоящее время, в принципе не позволяют достоверно определять их качественные и количественные параметры таких зон. Предлагаемый подход к решению проблемы является перспективным направлением междисциплинарного исследования природных феноменов. Ключевые слова: прибор, аномальные зоны, геопатогенные зоны, резонансы Шумана, электромагнитное поле, программно-аппаратный комплекс, микропульсации, стохастический резонанс.